Current Issues of Gastroenterology in Indonesia - Marcellus Simadibrata; Randy Adiwinata (Interna Publishing, 2017)
Indonesia is one of the most populous developing countries in the world. Similar with other developing countries, Indonesia has been suffered from the high incidence of gastroenterology diseases that mainly due to infection. In the recent years, Indonesia had also increased number of non-infectious gastroenterology diseases cases such as inflammatory bowel disease, gastroesophageal reflux disease, and colorectal cancer. Nevertheless, the developments of diagnostic and therapeutic modality along with the cooperation between sectors have undergone rapid progress as an effort in improving digestive health in Indonesia.